Genetic Diversity Analysis of Cysteine Proteinase B Gene in Leishmania major Isolates from Southwest Iran - Mahmoud Rahdar; Mohammad Reza Maghsoudi; Molouk Beiromvand; Tahereh Kardooni (Türkiye Parazitoloji Dergisi, 2025)
Objective: Selecting an effective target for Leishmania vaccination requires identifying a protein antigen with low or no genetic diversity. The cysteine proteinase B (CPB) gene has emerged as a promising immunogenic target, though its diversity requires evaluation across different regions. Given Iran’s status as a hyperendemic region for cutaneous leishmaniasis, this study aimed to collect and analyze 30 Leishmania major isolates from various areas of Khuzestan Province in Southwestern Iran. Methods: The CPB gene was amplified via polymerase chain reaction, and its nucleotide sequence was determined. Sequence analysis was performed using MEGA5 software, with subsequent comparison to National Center for Biotechnology Information database entries. A phylogenetic tree was constructed to compare isolated strains with reference strains from other geographic regions and species. Results: The phylogenetic analysis demonstrated that the CPB gene of the isolated strains in different regions of Khuzestan province formed a clade with certain Leishmania major strains from various parts of the world. Overall, the genotypic analysis of the CPB gene in Khuzestan province indicated genetic similarity among 29 isolates. In contrast, one sample from Dezful (north of Khuzestan Province) exhibited a significant difference from the reference strain, resulting in notable amino acid changes. Conclusion: Based on these findings, the CPB gene holds promise as a potential candidate for vaccination development against cutaneous leishmaniasis in this region.